2022
DOI: 10.1016/j.eujim.2022.102100
|View full text |Cite
|
Sign up to set email alerts
|

Perception, knowledge and attitude towards influenza vaccine during COVID-19 pandemic in Jordanian population

Abstract: Introduction Seasonal influenza is considered as one of the major causes of morbidity and mortality worldwide. This needs solutions to decrease burdens on the healthcare systems especially during the Coronavirus Disease (COVID-19) pandemic. Population knowledge, perception and attitude towards influenza vaccine during COVID-19 pandemic could have a positive impact to decrease mortality, morbidity and burdens on the healthcare system. This study focuses on investigating knowledge, attitude and prac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Studies showed that people with a co-infection of seasonal influenza and COVID-19 had much higher risk of mortality than those with neither influenza nor COVID-19 or with COVID-19 only [ 12 , 13 , 14 ]. It is suggested that SIV could help reduce the risk and severity of COVID-19 [ 15 , 16 , 17 ]. In addition, SIV has been considered as a protective factor against cardiovascular morbidity and mortality in patients with COVID-19 [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies showed that people with a co-infection of seasonal influenza and COVID-19 had much higher risk of mortality than those with neither influenza nor COVID-19 or with COVID-19 only [ 12 , 13 , 14 ]. It is suggested that SIV could help reduce the risk and severity of COVID-19 [ 15 , 16 , 17 ]. In addition, SIV has been considered as a protective factor against cardiovascular morbidity and mortality in patients with COVID-19 [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…A 2019 study concluded that older adults in Jordan exhibited a negative attitude toward the vaccine [ 10 ]. Additionally, during the COVID-19 pandemic, Jordanians were found to have low intentions of receiving the influenza vaccine, reaching only 27.7% [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Social media platforms may have the potential to publicize influenza vaccine information, and may encourage users to get vaccinated annually. Another factor that may explain the higher influenza vaccination rate in the 2021–2022 study may be the ability of the COVID-19 pandemic to renew awareness of respiratory infections, primarily influenza, an observation highly probable and widely reported in the literature [ 25 , 26 , 27 , 28 ], with popuar perceptions of the influenza vaccine during COVID-19 pandemic having positive impact on the influenza vaccine [ 29 ]. Specifically, the university health committee, established early during COVID-19, may have exercised a specific influence on university students by extensive awareness campaigns on COVID-19 [ 30 ], but this remains inconclusive and cannot be directly assessed using our results.…”
Section: Discussionmentioning
confidence: 99%